The Effects of Three Mineral Nitrogen Sources and Zinc on Maize and Wheat Straw Decomposition and Soil Organic Carbon - Ogunniyi Jumoke Esther, GUO Chun-hui, TIAN Xiao-hong, LI Hong-yun, ZHOU Yang-xue (National Key Laboratory of Integrated Management of Crop Diseases and Pests, Ministry of Education/College of Plant Protection, Nanjing Agricultural University, Nanjing 210095, P.R.China) (Journal of Integrative Agriculture, 2014)
The incorporation of straw in cultivated ifelds can potentially improve soil quality and crop yield. However, the presence of recalcitrant carbon compounds in straw slow its decomposition rate. The objective of this study was to determine the effects of different nitrogen sources, with and without the application of zinc, on straw decomposition and soil quality. Soils were treated with three different nitrogen sources, with and without zinc： urea （CO（NH2）2）, ammonium sulfate （（NH4）2SO4）, and ammonium chloride （NH4Cl）. The combined treatments were as follows：maize （M） and wheat （W） straw incorporated into urea-, ammonium sulfate-, or ammonium chloride-treated soil （U, S, and C, respectively） with and without zinc （Z） （MU, MUZ, WU, WUZ;MS, MSZ, WS, WSZ;MC, MCZ, WC, WCZ, respectively）;straw with zinc only （MZ, WZ）;straw with untreated soil （MS, WS）;and soil-only or control conditions （NT）. The experiment consisted of 17 treatments with four replications. Each pot contained 150 g soil and 1.125 g straw, had a moisture content of 80%of the ifeld capacity, and was incubated for 53 days at 25°C. The rates of CO2-C emission, cumulative CO2-C evolution, total CO2 production in the soils of different treatments were measured to infer decomposition rates. The total organic carbon （TOC）, labile organic carbon （LOC）, and soil microbial biomass in the soils of different treatments were measured to infer soil quality. All results were signiifcantly different （P〈0.05） with the exception of the labile organic carbon （LOC）. The maize and wheat straw showed different patterns in CO2 evolution rates. For both straw types, Zn had a synergic effect with U, but an antagonistic effect with the other N sources as determined by the total CO2 produced. The MUZ treatment showed the highest decomposition rate and cumulative CO2 concentration （1 120.29 mg/pot）, whereas the WACZ treatment had the lowest cumulative CO2 concentration （1 040.57 mg/pot）. The addition of NH4Cl resulted in the highest total organic carbon （TOC） concentration （11.59 mg kg-1）. The incorporation of wheat straw resulted in higher microbial biomass accumulation in soils relative to that of the maize straw application. The results demonstrate that mineral N sources can affect the ability of microorganisms to decompose straw, as well as the soil carbon concentrations.